Depression, Suicidal Ideation and Perceived Stress in Italian Humanities Students: A Cross-Sectional Study. Issue 1 (February 2022) - Bert, Fabrizio; Ferrara, Maria; Boietti, Edoardo; Langiano, Elisa; Savatteri, Armando; Scattaglia, Marco; Lo Moro, Giuseppina; Leombruni, Paolo; De Vito, Elisabetta; Siliquini, Roberta
Mental health issues are common among university students. Nevertheless, few studies focused on Italian students. This study aimed to assess prevalence and associated factors of perceived stress (PS), depressive symptoms (DS) and suicidal ideation (SI) in an Italian sample. A cross-sectional study was conducted amongst a convenience sample of students in humanities field (2018). Questionnaires were self-administered. Outcomes were assessed through Beck Depression Inventory-II (DS, SI) and Perceived Stress Scale (PS). Multivariable regressions were performed (p-value < 0.05 significant; sample size = 203). DS and SI prevalence was 30.6% and 8.8%. PS median score was 20 (IQR = 11), 87.7% reported moderate/severe PS. DS likelihood was increased by psychiatric disorders family history and not attending first year of course and decreased by not thinking that university hinders personal activities. Chronic disease and higher stress score increased SI probability; good/excellent family cohesion reduced it. Being female, thinking that university hinders resting/relaxing, seeing a psychologist/psychiatrist were positively associated with PS; having no worries about future was negatively associated. A high prevalence of mental health issues was reported, with miscellaneous associated factors that were linked to both private and social aspects. Universities must be aware of this to provide efficient preventive measures.